Gut microbiome and metabolic activity in type 1 diabetes: An analysis based on the presence of GADA - Luo, Sihui; Yue, Tong; Liu, Ziyu; Yang, Daizhi; Xu, Mengyun; Ding, Yu; Jiang, Weiwei; Xu, Wen; Yan, Jinhua; Weng, Jianping; Zheng, Xueying (Frontiers in Endocrinology, 2022)
Objective: Type 1 diabetes (T1D) progression is affected by circulating glutamic acid decarboxylase antibody (GADA) that persist for many years. This study aimed at investigating whether and how the gut microbiome and its correlated metabolites change in T1D with the presence of GADA. Methods: We used a radiobinding assay to measure GADA titers and identify the GADA+ ones (n=49) in 101 T1D patients. The fresh fecal and serum were analyzed using 16S rRNA gene sequencing and GC/MS. Then gut microbiome and serum metabolites were compared between the GADA+ patients and the GADA- ones. The association between gut microbial community and metabolites was assessed using the Spearman's rank correlation. Results: The gut microbiome in diversity, composition, and function differed between these two groups. The abundance of genus Alistipes, Ruminococcus significantly increased in patients with GADA compared to that observed in the samples of GADA-. For the untargeted serum metabolites, compared with those of GADA-, there were 54 significantly different metabolites with tryptophan metabolism, phenylalanine, and tyrosine and tryptophan biosynthesis decreased in individuals with GADA+. The abundance of Alistipes was positively correlated with altered metabolites involved in tryptophan metabolism. Conclusion: We demonstrate that T1D patients with GADA+ are characterised by aberrant profiles of gut microbiota and serum metabolites. The abundance of Alistipes disturbances may participate in the development of T1D patients with GADA by modulating the host’s tryptophan metabolism. These findings extend our insights into the association between the gut microbiota and tryptophan metabolism and GADA and might be targeted for preventing the development of T1D.